(untitled) (ENTHYMEMA, 2010)
De Sanctis wrote his Storia della letteratura italiana like a great popular novel of the 19th century, as a comparison with his Cesare Cantù e la letteratura popolare (from his 1872 Neapolitan lecture) can make clear. In elaborating the Storia, De Sanctis followed the compositional principles for «popular» literature not merely in the «surface of form», but also in those aspects that pertain to its «essential parts» and its «substance». The structure itselfof the Storia, by chronicling the evolution of Italian spirit through literary history, makes the work effective in De Sanctis’s prospective, as a means of spreading a unitary national conscience.